DCST1-AS1 Promotes TGF-β-Induced Epithelial–Mesenchymal Transition and Enhances Chemoresistance in Triple-Negative Breast Cancer Cells via ANXA1 - Tang, Li; Chen, Yuli; Chen, Huanhuan; Jiang, Pan; Yan, Linping; Mo, Dongping; Tang, Xun; Yan, Feng (Frontiers in Oncology, 2020)
Triple-negative breast cancer (TNBC) is a highly metastatic breast cancer subtype, and the primary systemic treatment strategy involves conventional chemotherapy. DC-STAMP domain containing 1-antisense 1 (DCST1-AS1) is a long noncoding RNA that promotes TNBC migration and invasion. Studying the role of DCST1-AS1 in promoting epithelial-mesenchymal transition (EMT) and chemoresistance will provide a new strategy for TNBC therapy. In the present study, we found that DCST1-AS1 regulates the expression or secretion of EMT-related proteins E-cadherin, snail family zinc finger 1 (SNAI1), vimentin, matrix metallopeptidase 2 (MMP2), matrix metallopeptidase 9 (MMP9). Interference with DCST1-AS1 impaired TGF-β-induced TNBC cell invasion and migration. DCST1-AS1 directly binds to ANXA1 in BT-549 cells and affects the expression of ANXA1. DCST1-AS1 enhances TGF-β/Smad signaling in BT-549 cells through ANXA1 to promote EMT. The combination of DCST1-AS1 and ANXA1 also contribute to enhancement of the resistance of BT-549 cells to doxorubicin and paclitaxel. In conclusion, DCST1-AS1 promotes TGF-β-induced EMT and enhances chemoresistance in TNBC cells through ANXA1, and therefore represents a potentially promising target for metastatic breast cancer therapy.